2017
DOI: 10.1038/cdd.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Germline BAP1 mutations induce a Warburg effect

Abstract: Carriers of heterozygous germline BAP1 mutations (BAP1+/−) develop cancer. We studied plasma from 16 BAP1+/− individuals from 2 families carrying different germline BAP1 mutations and 30 BAP1 wild-type (BAP1WT) controls from these same families. Plasma samples were analyzed by liquid chromatography time-of-flight mass spectrometry (LC-TOF-MS), ultra-performance liquid chromatography triple quadrupole mass spectrometry (UPLC-TQ-MS), and gas chromatography time-of-flight mass spectrometry (GC-TOF-MS). We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 54 publications
4
94
0
1
Order By: Relevance
“…Recent experiments, however, showed a novel BAP1 cytoplasmic activity: wt BAP1 localizes at the endoplasmic reticulum, and has a role in promoting apoptosis via Ca2+ mitochondrial changes . Moreover, it was shown that cells from individuals carrying heterozygous germline BAP1 mutations have a distinctive metabolic signature, consisting in impairment of mitochondrial respiration and increase of aerobic glycolysis leading to a Warburg effect . Metastatic potential and prognosis in UM lacking BAP1 functions could be influenced also by these mechanisms, Warburg effect creating an environment that promotes tumor growth in hypoxia, and impaired apoptosis increasing the resistance to chemotherapy‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments, however, showed a novel BAP1 cytoplasmic activity: wt BAP1 localizes at the endoplasmic reticulum, and has a role in promoting apoptosis via Ca2+ mitochondrial changes . Moreover, it was shown that cells from individuals carrying heterozygous germline BAP1 mutations have a distinctive metabolic signature, consisting in impairment of mitochondrial respiration and increase of aerobic glycolysis leading to a Warburg effect . Metastatic potential and prognosis in UM lacking BAP1 functions could be influenced also by these mechanisms, Warburg effect creating an environment that promotes tumor growth in hypoxia, and impaired apoptosis increasing the resistance to chemotherapy‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cells from BAP1 mutation carriers do not need to go through a selection process that favours the emergence of clones with a Warburg effect required for tumor growth: BAP1 +/− cells constitutionally derive a large part of their metabolism through aerobic glycolysis. Thus when these cells develop mutations they are already primed for cancer growth [158].…”
Section: Irbit a New Sensor For The Environment Interaction: Novel Omentioning
confidence: 99%
“…Germline mutations in BAP1 greatly enhanced the sensitivity of mice to develop mesothelioma when exposed to asbestos [50]. Recently, it has been shown in patient fibroblasts that loss of BAP1 displayed a metabolic rewiring towards aerobic glycolysis and reduced mitochondrial respiration associated with malignancy and carcinogenesis [51]. BAP1 was therefore identified as a novel IP 3 R3-interacting protein that impacts its post-translational modification.…”
Section: Comment Onmentioning
confidence: 99%